CTNI-72. PHASE 2 STUDY OF DIANHYDROGALACTITOL (VAL-083) IN PATIENTS WITH MGMT-UNMETHYLATED, BEVACIZUMAB-NAÏVE GLIOBLASTOMA IN THE RECURRENT AND ADJUVANT SETTING. (9th November 2020) - O'Brien, Barbara; Penas-Prado, Marta; Kamiya-Matsuoka, Carlos; Weathers, Shiao-Pei; Yung, W K Alfred; Loghin, Monica; Harrison, Rebecca; Majd, Nazanin; Bacha, Jeffrey; Brown, Dennis; Johnson, Greg; Langlands, John; et al.
Abstract: Current standard-of-care for glioblastoma (GBM) includes surgery followed by concurrent therapy with radiation and temozolomide (TMZ) followed by adjuvant TMZ. Almost all GBM patients experience recurrent/progressive disease despite upfront standard of care treatment, with a median survival after recurrence of 3–9 months. Unmethylated promoter for O 6 -methylguanine-DNA-methyltransferase (MGMT) is a validated biomarker for TMZ-resistance and is correlated with poor patient prognosis. VAL-083 is a bi-functional DNA-targeting agent which rapidly induces inter-strand cross-links at N 7 -guanine inducing double-strand breaks causing cell death and acts independent of MGMT DNA repair. This trial is an open-label two-arm biomarker-driven phase 2 clinical trial in MGMT-unmethylated bevacizumab-naïve GBM patients with either recurrent (Group 1) or newly diagnosed GBM requiring adjuvant therapy after chemo-radiation with temozolomide (Group 2). Patients receive VAL-083 IV at 30 or 40 mg/m 2 /d on days 1, 2, and 3 of a 21-day cycle. The primary objective of this study is to determine the effect of VAL-083 on median overall survival (mOS) in MGMT-unmethylated recurrent GBM patients (Group 1); and progression-free survival (PFS) in newly diagnosed GBM patients requiring adjuvant therapy after chemo-irradiation with temozolomide (Group 2), compared to historical controls in both groups. Tumor response will be assessed by MRI every 42 days, using RANO criteria. The initial starting dose in this study was 40 mg/m 2 /d on days 1, 2, and 3 of a 21-day cycle, which was subsequently reduced to 30 mg/m 2 /d to improve tolerance due to myelosuppression. As of June 2-2020, 35 patients with recurrent GBM (Group 1) have received 40 mg/m 2 /d and 39 patients have received 30 mg/m 2 /d VAL-083. In the adjuvant setting (Group 2), 25 patients have been enrolled (30 mg/m 2 /day). Enrollment, safety data and study updates will be presented at the meeting. Clinicaltrials.gov identifier: NCT02717962.